The role of vertical roof intrusion and post-crash headroom in predicting roof contact injuries to the head, neck, or face during FMVSS no. 216 rollovers : an updated analysis - Strashny, Alexander; United States. National Highway Traffic Safety Administration; National Center for Statistics and Analysis (U.S.). Mathematical Analysis Division ([Washington, D.C.] : National Highway Traffic Safety Administration, 2007)
The purpose of this report is to use the National Automotive Sampling System Crashworthiness Data System (NASS CDS) data for years 1997 through 2005 to determine whether there was a statistically significant relationship between the maximum severity of head, neck, and face injuries due to occupant roof contact that occurred in rollovers that were likely to be covered by Federal Motor Vehicle Safety Standard No. 216 and either post-crash headroom or vertical roof intrusion. The report uses the ordered probit and binary probit models, both unadjusted and adjusted for potentially confounding factors, to establish the existence of statistically significant relationships. The report presents estimates of 24 different models, 12 for intrusion and 12 for headroom. In all 24 models, the relationship between injury severity and the explanatory variable (intrusion or headroom) was statistically significant.
"Performing organization code: NVS-421"--Tech. report doc. p.
"DOT HS 810 847."
"October 2007."
Includes bibliographical references (p. 45-48).
Final report.
Also available online.
Keywords: Vehicle roofs; Deformation; Deflection; Accident severity; Rollover Accidents; National Accident Sampling System/ National Crash Severity Study; Deformation/ Deflection; Crush; Roofs; Rollover vehicle accidents; Neck -- Wounds and injuries; Head -- Wounds and injuries; Face -- Wounds and injuries; Crash injuries